Use of Electronic Media for the Promotion of Notaries According to the Notary Code of Ethics - Puteri Chintami Oktavianti (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The purpose of this study is to determine the problems that arise in the use of electronic media for the promotion of notaries according to the notary code of ethics. The research method used is that this type of research is juridical normative, which refers to the norms of written law, either as outlined in the form of regulations or in the form of literature. The approach used is a conceptual approach and a statutory approach. The analysis is descriptive qualitative, which collects and selects legal material according to the problem under study, then describes it so that it produces a picture or conclusion that matches the actual situation so that it is able to answer all existing problems. The results show that the existence of a promotion prohibition for notaries is based on the fact that a notary as a position that provides services to the community requires the trust of the people it serves, and the notary's existence is not for the personal benefit of the person appointed, so that the notary must uphold the nobility of his dignity. In promotions that are informative and reminders, it is permissible to, among others, provide information and knowledge about legal issues; case review of legal problems in the world of notary; examples of notary deeds.